A Cross Sectional Study on Assessment of Cognitive Impairment and Behavioural Risk Factors Among Senior Citizens Living in Old Age Homes in Chengalpattu District, Tamilnadu - Pandian, Sujitha; Swetha NB; Umadevi R; Grace G, Angeline; Gopalakrishnan S (National Journal of Community Medicine, 2022)
Background: Ageing is an irreversible, unavoidable, universal phenomenon accompanied by gradual reduction in functional capacity of the elderly. The number of elderly populations in India is expected to triple reaching 2 billion. This study aims to estimate the prevalence of cognitive impairment and evaluate the association between various socio demographic and behavioural risk factors. Methodology: This descriptive cross-sectional study was carried among 330 senior citizens living in old age homes by using a two-stage multistage sampling method. A standardized pretested structured questionnaire containing Brief Interview for Mental Status (BIMS) scale was used. Data was analysed using SPSS (Version 22). Results: Among 330 study respondents, around 44% had mild -to- moderate cognitive impairment and 36% had severe cognitive impairment. Nearly 74.8% have their habit of regular physical activity. Among the study subjects approximately 4% of them were current smokers, 5.2% had the habit of regular alcohol consumption previously. Conclusion: Integration of NPHCE and NMHP can be beneficial in early diagnosis of mild cognitive impairment during weekly outpatient visits at PHC. Level of attention given towards Alzheimer’s disease is more when compared to screening for cognitive impairment which is an early precursor for Alzheimer’s Disease.